The Syntactic Diversity Of SAuxOV In West Africa - Sande, Hannah; Baier, Nico; Jenks, Peter (My University, 2019)
Surface SAuxOV orders abound in West Africa. We demonstrate that apparent examples of this word order have important structural differences across languages. We show that SAuxOV orders in some languages are due to mixed clausal headedness, consisting of a head initial TP and head-final VP, though this order can be concealed by verb movement. Other languages are more consistently head-initial, and what appear to be SAuxOV orders arise in limited syntactic contexts due to specific syntactic constructions such as object shift or nominalized complements. Finally, we show that languages which have genuine SAuxOV, corresponding to a head-final VP, tend to exhibit head-final properties more generally. This observation supports the idea that syntactic typology is most productively framed in terms of structural analyses of languages rather than the existence of surface word orders.
Keywords: syntactic diversity; SAuxOV; West Africa